2017
DOI: 10.1111/dmcn.13367
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the Movement Assessment Battery for Children ‐ Second Edition at 4 years, for motor impairment at 8 years in children born preterm

Abstract: The MABC-2 at 4 years is predictive of motor functioning in middle childhood. Below average cognition and higher medical risk may be predictors of motor impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…14,16,17 In particular, the MABC-2 at 4 years has been shown to be predictive of motor functioning in middle childhood. 26 Fourth, WMI volume, which is a key contributor to neurodevelopment in preterm newborns, was systematically accounted for. 21 Fifth, we took a conservative approach in our analysis by setting a ceiling to CBH volume so as not to skew the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,16,17 In particular, the MABC-2 at 4 years has been shown to be predictive of motor functioning in middle childhood. 26 Fourth, WMI volume, which is a key contributor to neurodevelopment in preterm newborns, was systematically accounted for. 21 Fifth, we took a conservative approach in our analysis by setting a ceiling to CBH volume so as not to skew the results.…”
Section: Discussionmentioning
confidence: 99%
“…Motor impairment was defined as a total MABC-2 score of <5th percentile. 26 Psychology personnel administered the Beery-Buktenica Developmental Test of Visual-Motor Integration, 6th Edition (Beery VMI-6) 27 and WPPSI-III. 28 Overall indices of the Beery VMI-6 and WPPSI-III full-scale intelligence quotient (FSIQ) are standard scores with mean (standard deviation [SD]) of 100 (15), and impairment was defined as a score < 1 SD below the mean.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Recent work by Lee and colleagues failed to find similar cerebellar volume associations with 4-year outcomes (17), suggesting the consequences of early cerebellar deficits may not be evident until later in childhood. While some aspects of development and performance at age 4 years should be reasonably aligned with performance at age 7, such as for example motor performance and related developmental coordination disorders (55), differences within IQ, language complexity and attention are more likely to be detected later in childhood, coinciding with the expanded and increasing academic and cognitive demands associated with school age. Importantly, assessment of these aspects of development is limited in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its value as a measure of current difficulties, the MABC-2 Test has also been shown to have good predictive value. For instance, Griffiths et al (2017) found that the Test results of preterm children, examined at 4 years of age, accurately predicted their motor status at 8 years. One of the reasons for the popularity of the MABC-2 Test is that its structure and mode of administration make it easy to use and enjoyable for children to perform.…”
Section: Introductionmentioning
confidence: 99%